Graft copolymerization of methyl methacrylate onto sago starch using ceric ammonium nitrate and potassium persulfate as redox initiator systems - Fakhru'L‐Razi, A.; Qudsieh, Isam Y. M.; Wan Yunus, Wan Md Zin; Ahmad, Mansor; Ab. Rahman, Mohamad Zaki (Wiley, 2001)
The graft copolymerization of methyl methacrylate (MMA) onto sago starch was carried out in aqueous media by different initiators of ceric ammonium nitrate (CAN) and potassium persulfate (PPS) and under a nitrogen gas atmosphere. Using CAN as an initiator, the maximum percentage of grafting (%G) was ascertained to be 246% at the following optimum conditions: a 70°C reaction temperature, a 2-h reaction period, 2.0 mmol of CAN, 0.4 mmol of nitric acid, and 141 mmol of MMA. The maximum %G achieved with PPS as the initiator was 90%. The optimum conditions were a 50°C reaction temperature, a 1.5-h reaction period, 47 mmol of monomer, and 1.82 mmol of PPS. The grafting of MMA onto sago starch was confirmed by the IR spectra of pure sago starch, MMA, and MMA grafted sago starch. This material may have application as a biodegradable plastic.